Effect of MHD on unsteady oscillatory couette flow through porous media - Sharma, Bhupendra K.; Sharma, Pawan Kumar; Chauhan, Sudhir Kumar (Zielona Góra: Uniwersytet Zielonogórski)
This paper describes the effects of a magnetic field on unsteady free convection oscillatory systems. When temperature and species concentration fluctuate with time around a non-zero constant, "Couette flow" across a porous medium occurs. The system of non-linear ODEs that governs the flow is solved analytically using the perturbation approach because the amplitude of fluctuations is very tiny.
Keywords: MHD; porous media; free convection; Couette flow